2016
DOI: 10.1021/acs.analchem.6b00080
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variations of Explosive Residue Particles and Implications for Understanding Detonation Mechanisms

Abstract: The possibility of recovering undetonated explosive residues following detonation events is well-known; however, the morphology and chemical identity of these condensed phase postblast particles remains undetermined. An understanding of the postblast explosive particle morphology would provide vital information during forensic examinations, allowing rapid initial indication of the explosive material to be microscopically determined prior to any chemical analyses and thereby saving time and resources at the cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Recent works [72,73] have explored the formation of particles in two other different situations, i.e. welding fume particles originating from both the core and the covering of electrodes used in popular manners of welding steel and aluminium alloy constructions and post-blast explosive particles related to both inorganic and organic reactive materials.…”
Section: Resultsmentioning
confidence: 99%
“…Recent works [72,73] have explored the formation of particles in two other different situations, i.e. welding fume particles originating from both the core and the covering of electrodes used in popular manners of welding steel and aluminium alloy constructions and post-blast explosive particles related to both inorganic and organic reactive materials.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have characterized postdetonation particles using a variety of techniques. Steel witness plates surrounding a point of detonation at varying distances have been used to determine particle mass, and to some extent size, from high-order detonations of conventional explosives (Abdul-Karim, Blackman, Gill, and Karu 2016;Abdul-Karim, Blackman, Gill, Morgan, et al 2016;Borusiewicz et al 2013). Abdul-Karim, Blackman, Gill, and Karu (2016) found preliminary evidence for particle mass to relate to the inverse square of the distance from detonation, and they also found that mass decreases with increasing distance.…”
Section: Figures and Tablesmentioning
confidence: 99%
“…Ballistic experts may also collect bullets, projectile fragments and evidence from explosive discharge residues from the body of the victim. Explosive traces should be analyzed by a forensic chemical expert in order to define the typology of explosive material [57]. Moreover, residual particles may be searched through the use of Scanning Electron Microscopy/Energy Dispersive X-Ray Spectroscopy (SEM/EDX), which allows different classes of particles to be defined according to their composition and images [5,58].…”
Section: Autopsy Proceduresmentioning
confidence: 99%